2018
DOI: 10.1093/femsle/fny018
|View full text |Cite
|
Sign up to set email alerts
|

The solute transport profile of two Aza-guanine transporters from the Honey bee pathogen Paenibacillus larvae

Abstract: Two nucleobase transporters encoded in the genome of the Honey bee bacterial pathogen Paenibacillus larvae belong to the azaguanine-like transporters and are referred to as PlAzg1 and PlAzg2. PlAzg1 and 2 display significant amino acid sequence similarity, and share predicted secondary structures and functional sequence motifs with two Escherichia coli nucleobase cation symporter 2 (NCS2) members: adenine permease (EcAdeP) and guanine-hypoxanthine permease EcGhxP. However, similarity does not define function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…To assess the thermodynamic aspect of the uptake of tZ, tZR, iP, and iPR in the BY-2 cells, we performed a series of accumulation assays in suspensions treated with 50 µM protonophore carbonyl cyanide 3-chlorophenylhydrazone (CCCP) in dimethyl sulfoxide (DMSO). CCCP uncouples electron transfer from oxidative phosphorylation (Cavari et al, 1967; Cunarro and Weiner, 1975; Heytler, 1963), thus inhibiting proton gradient-dependent transport processes (Alexander et al, 2018; Culos and Watanabe, 1983; Stoffer-Bittner et al, 2018). We performed the same assays using cells treated with the corresponding amount of DMSO alone (mock treatment) as control.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the thermodynamic aspect of the uptake of tZ, tZR, iP, and iPR in the BY-2 cells, we performed a series of accumulation assays in suspensions treated with 50 µM protonophore carbonyl cyanide 3-chlorophenylhydrazone (CCCP) in dimethyl sulfoxide (DMSO). CCCP uncouples electron transfer from oxidative phosphorylation (Cavari et al, 1967; Cunarro and Weiner, 1975; Heytler, 1963), thus inhibiting proton gradient-dependent transport processes (Alexander et al, 2018; Culos and Watanabe, 1983; Stoffer-Bittner et al, 2018). We performed the same assays using cells treated with the corresponding amount of DMSO alone (mock treatment) as control.…”
Section: Resultsmentioning
confidence: 99%
“…The broad solute recognition of PlUacP is reminiscent of some bacterial NCS2 COG2252 and some eukaryotic NCS2 transporters. Recently, it was shown that two AzgA‐like transporters of P. larvae , PlAzg1 and PlAzg2, belonging to COG2252, display a wide solute transport profile including adenine, guanine, xanthine, uracil, and cytosine . Eukaryotic NCS2 transporters have similarly broad transport profiles including A. nidulans AzgA transporting adenine, guanine, and hypoxanthine ; Arabidopsis thaliana Azg1 and Azg2 transporting adenine and guanine; Zea mays Azg2–Azg3 transporters transporting adenine, guanine, cytosine, hypoxanthine, and xanthine (Mourad and Schultes, pers.…”
Section: Resultsmentioning
confidence: 99%